REINFORCEMENT CREATIVE THINKING ABILITIES OF MADRASAH ALIYAH STUDENTS THROUGH GUIDED DISCOVERY COMBINED WITH BRAINSTORMING IN BIOLOGY - Muhamad Wajid Wardana; Riezky Maya Probosari; Murni Ramli; Suwarti Suwarti (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2018)
This research aims to reinforce students' creative thinking ability in MAN 2 Kebumen by applying guided discovery learning combined with brainstorming. This study is a Classroom Action Research has been done in three cycles. Each cycle consisted of planning, action, observation, and reflection follow the spiral method of Kemmis & Taggart. The subjects were 32 students of grade tenth MIA 1 of MAN 2 Kebumen academic in year 2017/2018. The data research obtained through observation, interviews, and test. Data was analysis by qualitative descriptive techniques. Data validation use triangulation techniques. The results shows that implementation of guided discovery learning combined with brainstorming can reinforce students’ creative thinking ability. Reinforce of the thinking ability of students can be seen through cognitive test result. The result shown that average students’ creative thinking ability score at pre-cycle was 31,64%, the first cicle was 37,30%, the second cycle was 46,87%, and the third cycle was 48,43%. Conclusion of this research is guided discovery learning combined with brainstorming were able to reinforce creative thinking ability students grade tenth MIA 1 of MAN 2 Kebumen.